Debranched waxy maize resistant dextrin: Synthesis, ethanol fractionation, crystallization, and characterization. (1st February 2023) - Lee, Dong-Jin; Kim, Jong-Yea; Lim, Seung-Taik
Abstract: Waxy maize ( Zea mays L.) dextrins (WMD), prepared by enzymatic debranching, were fractionated through precipitation in different concentrations of aqueous ethanol (50 %, 60 %, and 80 %). The fractionated WMDs were then crystallized at 4 °C or 50 °C for 2 days to prepare resistant dextrins (RD). Recovery yield, chain distribution, crystalline structure, thermal transition, and in vitro digestibility of the fractionated/crystallized WMDs were evaluated. Crystallization at 4 °C resulted in higher yields (>90 %) than that at 50 °C, regardless of the fractionation condition. The chain profile of the dextrins recovered at different temperatures appeared similar, but the longer chains had a greater tendency to associate. Crystal arrangement (A- or B-type) depended on the fractionation and crystallization conditions. Most crystals showed a typical B-type arrangement, except for the crystals prepared at 50 °C with 80 % ethanol (A-type). The enzyme resistance ranged from 49.9 % to 92.4 % depending on the fractionation and crystallization conditions. Graphical abstract: Unlabelled Image